2012
DOI: 10.1166/jnn.2012.6662
|View full text |Cite
|
Sign up to set email alerts
|

Development and Stability of Innovative Semisolid Formulations Containing Nanoencapsulated Lipoic Acid for Topical Use

Abstract: The use of new cosmetic ingredients, unlike traditional hydrogels, represents a differentiated platform for preparation of stable semisolid formulations containing polymeric nanocapsules, presenting physicochemical properties suitable for topical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The healing of skin wounds is a complex and dynamic phenomenon of cellular structure restoration in injured tissues, in which multiple mechanisms and mediators are involved 12 . The role of substances with antioxidant properties in this scenario appears to be still controversial; some authors suggest that the excess of reactive oxygen species may slow the healing process 10 It was previously demonstrated that the nanocapsulation increases the physical and chemical stability, as well the antioxidant effect of lipoic acid 6,8 . In this study, although the nanoencapsulation did not provide additional benefits to wound healing, the data support the idea that this is a good technique not only to increase the antioxidant activity, but also to reduce the pro-oxidant activity of the compound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The healing of skin wounds is a complex and dynamic phenomenon of cellular structure restoration in injured tissues, in which multiple mechanisms and mediators are involved 12 . The role of substances with antioxidant properties in this scenario appears to be still controversial; some authors suggest that the excess of reactive oxygen species may slow the healing process 10 It was previously demonstrated that the nanocapsulation increases the physical and chemical stability, as well the antioxidant effect of lipoic acid 6,8 . In this study, although the nanoencapsulation did not provide additional benefits to wound healing, the data support the idea that this is a good technique not only to increase the antioxidant activity, but also to reduce the pro-oxidant activity of the compound.…”
Section: Discussionmentioning
confidence: 99%
“…Since the lipoic acid is a highly unstable compound, technological alternatives must be developed to permit its delivery in formulations that maintain its functional properties, to allow the topical use of lipoic acid. In this way, our previous reports demonstrated that the incorporation of lipoic acid in lipid-core nanocapsules improves its stability, allowing its formulation in semi-solid formulations, suitable for topical application 6,7 .…”
Section: Introductionmentioning
confidence: 94%
“…The PG formulation presented the highest viscosity variation after the thermal cycles, with an increase in viscosity as indicated by the values of K in Table 2. This behavior could be observed after the stress conditions in emulsions obtained from emulsifying and thickening polymers and waxes (Casteli et al, 2008;Guaratini et al, 2006;Külkamp-Guerreiro et al, 2012). The behavior is likely to be related to the evaporation of water from the formulations (Pianovski et al, 2008) causing an increase of thickening agent concentration (in this case, pinhão starch).…”
Section: Stability Of Semisolid Formulationsmentioning
confidence: 98%
“…Nanoemulsions Ultrasonic emulsification-solvent evaporation [5,6] Ultrasonication [7] Emulsification/evaporation [8] Lipid nanocarriers High pressure homogenization [9][10][11][12][13][14] High shear homogenization/high pressure homogenization [15] Melt emulsification coupled with high shear homogenization [16,17] Double emulsion [18] Hot melt microemulsion [19] Microemulsion coupled with probe sonication [20] Ultrasonication [7,21,22] Polymeric nanocarriers Ionic crosslinking [23] Interfacial deposition of pre-formed polymer [24,25] Polymerization of monomers [8] Emulsification/solvent evaporation [26,27] Two-step desolvation [28]…”
Section: Methods Referencesmentioning
confidence: 99%
“…Zeta potential reflects the particle surface charge and is related to its composition. Negative zeta values are the most reported [18,24,25]. Nevertheless, positive zeta potential is also reported for nanocarriers since there is an increase in its biological efficacy compared to negatively charged nanocarriers [29].…”
Section: Nanocarrier Characterizationmentioning
confidence: 99%